1968
DOI: 10.1126/science.162.3858.1146
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-5-(1-methyl-5-nitro-2-imidazolyl)-1,3,4-thiadiazole: A New Antimicrobial Agent

Abstract: The title compound has been prepared and shown to be highly active against a wide variety of gram-positive and gram-negative bacteria in mice and chicks, as well as against a number of parasitic infections in rodents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
0
23
0
1
Order By: Relevance
“…Megazol, a 2-substituted-5 nitroimidazole (MW 226) first described by Berkelhammer & Asato (1968) and synthetized by G. Chauvière, is almost insoluble in water but highly soluble in dimethylsulfoxide (DMSO). It can be administered either per os (PO) in 0.5% (w/v) carboxymethylcellulose (Merck) aqueous suspension or intraperitonally (IP) in DMSO (Prolabo).…”
Section: Drugsmentioning
confidence: 99%
“…Megazol, a 2-substituted-5 nitroimidazole (MW 226) first described by Berkelhammer & Asato (1968) and synthetized by G. Chauvière, is almost insoluble in water but highly soluble in dimethylsulfoxide (DMSO). It can be administered either per os (PO) in 0.5% (w/v) carboxymethylcellulose (Merck) aqueous suspension or intraperitonally (IP) in DMSO (Prolabo).…”
Section: Drugsmentioning
confidence: 99%
“…The examples of modeling with the use of WHIM descriptors could suggest their further use in prediction of activities of other compounds, like the set with antimicrobial activities in our research. Previous studies have shown the benefits of the use of ANN analysis in prediction of antimicrobial activity of different imidazole derivatives against many microorganisms [11,15,16]. Currently, the ANN predicted log1/MIC values were also significantly correlated with experimentally obtained log 1/MIC.…”
Section: Resultsmentioning
confidence: 59%
“…The increasing use of those models in sciences such as chemistry and biology has been noted since the 1980s. ANNs have been applied in the identification of potential drug targets, modeling of QSAR, compound classification and identification of potential drug candidates [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…2-Amino-5-( 1 -methyl-5-nitro-2-imidazolyl)-1,3,4-thiadiazol, called Megazol, was first synthesized by researchers from American Cyanamide [1]. Though encompassing a biological activity spectrum, Megazol was not developed due to possible mutagenicity [2,3].…”
Section: Introductionmentioning
confidence: 99%